Aqueous degradation of 6-APA by hydroxyl radical: a theoretical study - Aydogdu, Seyda; Hatipoglu, Arzu (SPRINGER, 2023)
ContextDegradation reactions of micropollutants such as antibiotics with OH radicals are very important in terms of environmental pollution. Therefore, in this study, the degradation kinetic mechanism of 6-aminopenicillanic acid (6-APA) with OH radical was investigated by density functional theory (DFT) methods.MethodsFor the calculations, different functionals such as B3LYP, MPW1PW91, and M06-2X were used with a 6-31 g(d,p) basis set. The aquatic effect on the reaction mechanism was investigated by conductor-like polarizable continuum model (CPCM). For the degradation kinetics in aqueous media, the addition of explicit water molecules was also calculated. Subsequent reaction mechanism for the most probable reaction product was briefly discussed.ResultsAmong the functionals used, B3LYP results were consistent with the experimental results. Calculated kinetic parameters indicated that the OH-addition path was more dominant than the H-abstraction paths. With the increase of explicit water molecules in the models, the energy required for the formation of transition state complexes decreased. The overall rate constant is calculated as 2.28 x 10(11) M-1 s(-1) at 298 K for the titled reaction.
Keywords: 6-Aminopenicillanic acid; Density functional theory; Hydroxyl radical; Kinetics; BETA-LACTAM ANTIBIOTICS; ADVANCED OXIDATION PROCESSES; SUBCRITICAL WATER OXIDATION; PHOTO-FENTON; WASTE-WATER; MECHANISM; REMOVAL; CEPHALEXIN; AMPICILLIN; TIO2; Biochemistry & Molecular Biology; Biophysics; Chemistry; Computer Science